QUALITY BY DESIGN-DRIVEN FORMULATION DEVELOPMENT AND OPTIMIZATION OF ENALAPRIL MALEATE LOADED MUCOADHESIVE MICROSPHERES: IN VITRO AND IN VIVO CHARACTERIZATION - KOMATI, SOMESHWAR; BHANOJI RAO, MUDDANA ESWARA; SWAIN, SURYAKANTA; GHOSE, DEBASHISH (International Journal of Applied Pharmaceutics, 2023)
Objective: The study is to formulate the enalapril maleate-loaded mucoadhesive microspheres with varied compositions of selected polymers for developing the oral controlled release formulations prepared by ionic gelation method and optimization through central composite design. Methods: Systematic optimization of microspheres was accomplished by the central composite design and characterized for particle size, entrapment efficiency, in vitro drug release and ex vivo mucoadhesion strength, which indicated that microspheres were a consequence to be spherical and free-flowing in nature. The microspheres exhibited high drug entrapment efficiency and in vitro drug release in a sustained manner, which was considered to be dependent on the concentration of rate-controlling polymers. The microspheres are showed 389.2 to 850 µm particle size and 22.36 to 85.22 % encapsulation efficiency. In vitro studies indicated optimized formulation showed 89.26% drug release after 12h and reduced blood pressure effectively. Results: The pharmacokinetic parameters were evaluated with Cmax of 75.39 µg/ml, tmax of 8h, and AUC of 53.55 µg/hr/ml, elimination rate constant of 0.0392 and t1/2 of 10h. The stability studies were conducted for 3 mo under various conditions and identified no significant deviations in selected key quality attributes. Conclusion: The formulated mucoadhesive microspheres of enalapril maleate tend to reduce the blood pressure in the animal model, with the novel drug delivery approach in the efficient management of hypertension.